Spontaneous Bladder Rupture: Demystifying the Condition – A Systematic Review - Reddy, Deshin (University of the Witwatersrand, Johannesburg, 2023)
Objectives: To perform a systematic review of all cases of spontaneous rupture of the urinary bladder (SRUB) and to describe the demographic data, associated co-morbidities, clinical presentation, diagnosis, relevant laboratory findings, associated factors, management, morbidity, and mortality associated with the presentation of SRUB. Methods: The study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO). A search was carried out across the following electronic databases: PubMed, Web of Science, Scopus, Google Scholar, and the Cochrane Database of Systematic Reviews. Full texts of selected studies were analysed, and data extracted. The review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: A total of 278 articles comprising 240 case reports and 38 case series, with a total of 351 patients were included. The median (IQR) age of all included patients was 47.5 (33-65) years. The median (IQR) time to presentation was 48 (24-96) hours, with the major presenting symptom being abdominal pain (76%). In patients in whom the diagnosis was made prior to any intervention, the condition was misdiagnosed in 64% of cases. The diagnosis was confirmed during explorative open surgery in 42% of cases. Pelvic radiation (13%) and alcohol intoxication (11%) were the most common associated factors. Intraperitoneal rupture (89%) was much more common with the dome of the bladder being most frequently involved (55%). The overall mortality was 15%. Conclusion: This review identified a number of key factors that appear to be associated with an increased incidence of SRUB. It also emphasised the high rate of misdiagnosis and challenges in confirming the diagnosis. Overall, it highlighted the importance of the need for increased awareness and maintaining a high index of suspicion for this condition.
A Research Report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Emergency Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Spontaneous bladder rupture; Idiopathic bladder rupture; Atraumatic bladder rupture; Uroperitoneum; Urinary ascites; Pseudo-renal failure; SRUB; Urology; UroTrauma; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education